P–174 Globulin-rich protein supplements improve blastulation efficiency in culture and promote implantation in vitro. (6th August 2021) - Ojosnegros, S; Seriola, A; Aroca, E; Godeau, A; Denkova, D; Casals, M
Abstract: Study question: Can globulin-rich compared to albumin (HSA) supplements improve blastulation and support embryo development towards post implantation? Summary answer: Yes, globulin supplements with clinical-grade quality increase blastulation efficiency by 20% (50% in older mothers) and support the transition of embryos towards post-implantation development. What is known already: During embryonic development at the morula stage there is a metabolic transition towards glycolysis as demand from outsourced energy increases. Therefore as cleavage proceeds, the demand for nutrients in the embryo increases accordingly. With few exceptions, HSA from human plasma or recombinant origin has been the main an only protein supplement used in almost all IVF-procedures. Globulin rich supplements are available but their use is not widespread and little is known about their efficiency in post-implantation development. Study design, size, duration: We have cultured more than 600 mouse embryos in continuous media containing a protein supplement#1 (PS#1), from 1-cell up to blastocyst stage. At blastocyst stage embryos were replaced into fresh media containing protein supplement#2 (PS#2). The embryos were allowed to hatch naturally and then transferred into a proprietary matrix for further development and implantation for an additional 48h. Participants/materials, setting, methods: The blastulation rate, measured for HSA-supplemented embryo cohort was compared with embryos cultured in PS#1. Hatching efficiency was reported for embryos cultured in transfer media including PS#2. Once embedded in the matrix, advanced label-free imaging techniques and custom algorithms to measure matrix implantation strength were used. Key molecular markers (i.e. OCT4, CDX2) for correct post-implantation lineage patterning were documented by conventional 3D confocal immunofluorescence imaging. Main results and the role of chance: Embryos supplemented with PS#1 reached blastocyst with overall 21% higher efficiency than embryos supplemented by HSA. When separated by age cohorts, embryos obtained from older females (ex-colony breeders, >14 weeks old) reached blastocyst stage with 55% higher efficiency than the same type of embryos cultured in the presence of HSA. Embryos obtained from females at optimal reproductive age reached blastocyst stage 10% more efficiently under PS#1 supplementation than with HSA. Hatching efficiency was 45% higher for embryos cultured with PS#2 than embryos supplemented with HSA. For every variable tested (e.g.% of arrested or degenerated embryos) or condition implemented (e.g. mouse basal media, human basal media from different brands, etc.) PS#1 and PS#2 outperformed, without exception, the supplementation with HSA. When embedded in the implantation matrix, the embryos cultured with PS#1 (cleavage) and transferred to PS#2 at blastocyst stage showed a remarkable implantation ability as measured by trophoblast outgrowth and matrix deformations. The embryos in PS#2 medium exerted stronger force into the matrix and also survived longer times than the embryos in HSA. PS#2 supported the transition of blastocyst towards post-implantation stages of development showing the correct lineage patterning of embryonic and extraembryonic molecular markers, including Oct4, CDx2, EOMES or GATA4. Limitations, reasons for caution: This is a study based on an animal model. These observations need to be confirmed by ongoing experiments with human embryos. Wider implications of the findings: This work constitutes a proof-of-concept for the use of globulin-rich supplements as higher performance substitute of albumin in the culture of IVF embryos, both as (i) a standard protein source for culture media and (ii) as a supplement for transfer media to capacitate the embryo for implantation. Trial registration number: Not applicable